On weighted multidimensional embeddings for monotone functions - Barza, Sorina; Persson, Lars-Erik; Stepanov, Vladimir D. (Mathematica Scandinavica, 2001)
We characterize the inequality 7817 \left(\int_{R^N_+} f^q u\right)^{1/q} ≤ C \left(\int_{R^N_+} f^p v \right)^{1/p},\,\,0